Transforming Regiocultural Branding into Sustainable Marketing Performance: A Dynamic Capability Perspective - Tatang Rois; Agapito Barros; Wachjuni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
In dynamic market environments, culture-based small and medium enterprises (SMEs) face the challenge of transforming local cultural identity into sustainable marketing performance. Although regiocultural branding enhances brand differentiation and authenticity, prior marketing studies often treat it as a static symbolic asset, offering limited explanation of how cultural values remain relevant under market change. Drawing on the dynamic capability perspective, this study develops and tests a process-based model explaining how regiocultural branding is transformed into sustainable marketing performance through dynamic marketing capabilities. Survey data from 200 owners or managers of culture-based SMEs were analysed using Structural Equation Modelling (SEM-AMOS). The results show that regiocultural branding positively affects dynamic marketing capabilities, which in turn significantly enhance sustainable marketing performance. Dynamic marketing capabilities partially mediate the relationship between regiocultural branding and sustainable marketing performance. This study reconceptualises regiocultural branding as a trigger for dynamic capability development rather than a static identity asset and extends the dynamic capability perspective to culture-based SME marketing in developing countries.